Behavior of single-box multi-cell box-girders with corrugated steel webs under pure torsion. Part II: Theoretical model and analysis. (August 2018) - Shen, Kongjian; Wan, Shui; Mo, Y.L.; Jiang, Zhengwen; Li, Xiayuan
Abstract: A theoretical model called unified softened truss model for torsion (USTMT) is presented in this study to analyze the full torsional behavior of single-box multi-cell box-girders with corrugated steel webs (BGCSWs) under pure torsion. The predicted results have good agreement with the experimental and FEA results from the companion paper and the newly built shear strain relations between the corrugated steel webs (CSWs) of multi-cell BGCSWs in the companion paper is proved to be reasonable and can be employed in the proposed model. The comparisons of various shear strain relations between concrete slabs and CSWs show the correctness of new assumption in the proposed model. The results also indicate that the tension stiffening effect of concrete cannot be ignored and it is necessary to correct the thickness of shear flow zone in concrete slabs. In addition, the parametric study shows that the torsional capacity is in linear proportion to compressive strength of concrete, the thickness and yield strength of CSWs in the properly designed range of parameters. The proposed model is capable to predict the full torsional behavior of multi-cell BGCSWs with no more than 10 cells. Highlights: A new model is proposed for the behavior of single-box multi-cell BGCSWs under pure torsion. Newly built shear strain relations between the CSWs in multi-cell BGCSWs is proved to be reasonable. A new shear strain relations between concrete slabs and CSWs is employed in the new model. The tension of concrete and the correction of effective thickness of concrete slabs are considered. A parametric study by the new model is conducted to evaluate the effect of various parameters.